2021
DOI: 10.1177/0960327121989412
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 protects hippocampal neurons from oxygen-glucose deprivation-induced injury through the AMPK/Nrf2/ARE pathway

Abstract: Objective: C1q/TNF-related protein 3 (CTRP3), a member of CTRP family, has been found to have neuroprotective effect. In the current study, we investigated the protective role of CTRP3 in hippocampal neurons exposed to oxygen-glucose deprivation/reperfusion (OGD/R). Materials and methods: The mRNA and protein levels of CTRP3 in OGD/R-stimulated hippocampal neurons were measured using qRT-PCR and western blot analysis, respectively. CCK-8 assay was performed to assess cell viability. ROS production was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…9 The overexpression of proliferator-activated receptor gamma coactivator-1α (PGC-1α) pathways in oxygen-glucose deprivation/reperfusion-induced hippocampal neurons. 34,35 Administration of CTRP3 reduced reactive oxygen species and malondialdehyde production, increased the level of glutathione, attenuated cerebral edema and BBB disruption, promoted angiogenesis, and improved neurological defects via both protein kinase A (PKA) and AMPK/hypoxia inducing factor-1α (HIF-1α)/vascular endothelial growth factor (VEGF)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The overexpression of proliferator-activated receptor gamma coactivator-1α (PGC-1α) pathways in oxygen-glucose deprivation/reperfusion-induced hippocampal neurons. 34,35 Administration of CTRP3 reduced reactive oxygen species and malondialdehyde production, increased the level of glutathione, attenuated cerebral edema and BBB disruption, promoted angiogenesis, and improved neurological defects via both protein kinase A (PKA) and AMPK/hypoxia inducing factor-1α (HIF-1α)/vascular endothelial growth factor (VEGF)…”
Section: Discussionmentioning
confidence: 99%
“…Lacking CTRP3 exacerbated depression‐type behaviors (e.g., decreased sucrose consumption and locomotor activity), neuronal death, expression of cleaved caspase‐3, and pro‐inflammatory responses by inhibiting p38 and Jun N‐terminal kinase (JNK)/mitogen‐activated protein kinase (MAPK) pathways in a depression mouse model 33 . The overexpression of CTRP3 attenuated oxidative stress, enhanced mitochondrial biogenesis, and induced changes in a series of regulatory molecules such as BCL‐2 expression, BAX expression, and Caspase‐3 activity via both AMPK/nuclear factor erythroid 2‐related factor 2 (NRF2)/antioxidant response element (ARE) and AMPK/SIRT1/peroxisome proliferator‐activated receptor gamma coactivator‐1α (PGC‐1α) pathways in oxygen–glucose deprivation/reperfusion‐induced hippocampal neurons 34,35 . Administration of CTRP3 reduced reactive oxygen species and malondialdehyde production, increased the level of glutathione, attenuated cerebral edema and BBB disruption, promoted angiogenesis, and improved neurological defects via both protein kinase A (PKA) and AMPK/hypoxia inducing factor‐1α (HIF‐1α)/vascular endothelial growth factor (VEGF) pathways in an intracerebral hemorrhage rat model 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) demonstrated that CTRP3 overexpression promoted cell proliferation and reduced apoptosis of AC16 cardiomyocytes treated with HG. Overexpression of CTRP3 attenuated the OGD/R-caused apoptosis with increased Bcl-2 expression and decreased Bax expression ( Ding, Wang & Song, 2021 ). These results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…CTRP3 is expressed in vascular smooth muscle cells at the cellular level ( Zhou et al, 2014 ). Recent studies have revealed that the expression level of CTRP3 decreases in the pathogenesis of acute injury in high glucose (HG)-induced H9C2 cells ( Ma et al, 2017 ) and oxygen-glucose deprivation/reoxygenation (OGD/R)-induced hippocampal neurons ( Ding, Wang & Song, 2021 ). Furthermore, several studies have shown that CTRP3 participated in neuroprotection and cardioprotection via reducing inflammatory response, apoptosis, and oxidative stress, suggesting that CTRP3 is a potentially protective factor ( Gao, Qian & Wang, 2020 ; Ma et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the important action of oxidative stress in the development of oxygen-glucose deprivation/reperfusion (OGD/RP)-which lead to neuronal injury, its strict regulation is a potential master plan for alleviating neuronal injury. 17,18 The Nrf2/ARE signaling pathway has emerged as a critical regulator pathway of neuronal oxidative injury and apoptosis. 19,20 Target genes of Nrf2 include proteins involved in the regulation of the synthesis of antioxidant proteins, drug-metabolizing enzymes, pentose phosphate pathway enzymes, and enzymes involved in nucleotide syntheses, such as heme oxygenase-1 (HO-1), glutathione-S-transferase (GST), quinone oxidoreductase-1 (NQO1), thioredoxins (Trxs), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px).…”
Section: Introductionmentioning
confidence: 99%